Effects of diurnal temperature fluctuations on growth performance, energy metabolism, stress response, and gut microbes of juvenile mud crab Scylla paramamosain - Liu, Jiahao; Chen, Shujian; Ren, Zhiming; Ye, Yangfang; Wang, Chunlin; Mu, Changkao; Wu, Qingyang; Shi, Ce (Frontiers in Marine Science, 2022)
A 51-day experiment was conducted to investigate the effects of diurnal temperature fluctuations (DTF) on growth performance, energy metabolism, stress response and gut microbiota of juvenile mud crab Scylla paramamosain. One control and three fluctuation groups were set up, i.e., constant (28 ± 0°C) (CT), slight (SF) (28 ± 2°C), medium (MF) (28 ± 4°C), and large (LF) (28 ± 6°C) DTF. The survival rate tended to decrease with the intensification of DTF, the survival of rate of CT, SF, MF and LF were 80.6 ± 3.9%, 75.0 ± 6.8%, 33.3 ± 6.8%, and 30.6 ± 10.4% respectively. The crab in SF and MF had a shorter, but LF had a longer molt interval compared with the crab in the CT group. Cortisol, blood glucose (GLU), total cholesterol (T-CHO) and triglyceride (TG) levels peaked in the LF group. The exacerbation of DTF caused a dramatic increase in reactive oxygen species (ROS) levels and impacted the antioxidant capacity of juvenile crabs. The relative expression of AMP-activated protein kinase (ampk), heat shock protein 70 (hsp70) and heat shock protein 90 (hsp90) genes was significantly increased in MF group. The expression of Ribosomal protein S6 kinase (s6k) and Mechanistic target of rapamycin (tor) genes was significantly up-regulated in the SF group (P< 0.05) but large DTF caused a decrease in the relative expression of a large number of functional genes. DTF affected the structure and function of gut microbes. The bacterial community changed with the intensification of DTF and alpha diversity continued to rise. Five biomarkers were identified, where Rhodobacterales and Rhodobacterac were significantly more abundant in the CT group, Campylobacterales,Vibrionales and erysipelotrichales were more abundant in the SF, MF and LF groups. In addition, SF also enhanced gut microbes interactions compared with other treatments. These results suggest that drastic environmental DTF reduced the growth and survival of young mud crabs, and the effect was mediated by energy metabolism, antioxidant pathways and gut microbes.